Synergistic Induction of Apoptosis by Quercetin and Curcumin in Chronic Myeloid Leukemia (K562) Cells - YALÇIN, AHMET SUHA; YILMAZ GÖLER, AYŞE MİNE (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2018)
Chronic myeloid leukemia is a major hematopoietic malignancy characterized by expansion of myeloid cells. In this study, we have investigated whether quercetin, curcumin and their combination induce apoptosis and inhibit growth of K562 cells. We have observed that quercetin and curcumin combination induced apoptosis accompanied by increased ROS and decreased GSH levels as well as loss of mitochondrial membrane potential. Our mRNA and protein expression results suggested that cytochrome c was released from mitochondria causing PARP and caspase-9 cleavages, the hallmarks of mitochondrial apoptotic pathway. We believe that triggering of apoptosis is mostly via mitochondrial pathway and ROS generation may induce impairment of mitochondrial membrane potential. The use of quercetin and curcumin combination potentiates individual apoptotic effects of the polyphenols and reduces their effective dose thereby preventing potential toxic effects on normal cells. Additional preclinical studies and clinical trials are certainly required to further validate their usefulness as potent anticancer agents.
Keywords: IN-VITRO; CYTOCHROME-C; CANCER-CELLS; ANTICANCER; DRUGS; PROLIFERATION; POLYPHENOLS; IMATINIB; AGENTS; DEATH